MISSIOLOGICAL DIMENSIONS FROM VATICAN II IN THE CONTEXT OF THE VIETNAMESE CHURCH: 50 YEARS AFTER - Cong, Jerome Nguyen Dinh (Asian Horizons, 2013)
Vatican II is seen as a great event initiating a colossal change with far-reaching repercussions in the Catholic Church in the 20th century. Fifty years later, its fruits continue to flourish in new and surprising ways and to mature in local churches worldwide. It is compared to a gust of fresh wind that has brought to the universal Church new vigour and new vistas. In other words it has compelled the Church to change her countenance in response to her mission in the modern world. This alteration is also being realized in the Vietnamese Church seeking a new vision and a new way of being Church. This article reflects on the response of the Vietnamese Church to the challenge Vatican II launched during these last 50 years. To do this, the opportunities and ordeals encountered will be presented. Finally, the paper will try to propose an approach to the current reality.